SOSIALISASI PENCEGAHAN PENYAKIT TBC UNTUK MENINGKATKAN KEPEDULIAN MASYARAKAT DALAM MENURUNKAN KASUS TBC DI DESA TANJUNG - Saputra, Dede; Anasrullah, Aldi; Ni Putu Eka Devi Meyrani, Pande; Kurnia, Kurnia; Tri Lestari, Andi (Universitas Mataram, 2025)
Tanjung Village is committed to becoming a Healthy Village where one of the challenges faced is the control and prevention of Tuberculosis (TB), which is caused by bacteria called Mycobacterium tuberculosis. Thi bacteria attacks the lungs and can attack other organs of the body if not treated properly. Therefore, the Tanjung 2 KKN Group held a TB Disease Prevention Socialization activity in Tanjung Village which aims to increase public awareness in reducing the number of TB cases. This activity involved the Tanjung 2 Village KKN PMD team, village government, health cadres, and medical personnel from the Tanjung Health Center. This socialization provided education about symptoms, causes, transmission methods, prevention steps, and the importance of complete treatment. The methods used included interactive presentations, educational video screenings, and discussion and question and answer sessions. The results of the activity showed an increase in public understanding of early detection and the importance of compliance in TB treatment. The high participation in the discussion session indicated the enthusiasm of residents and the need for further information. The obstacles faced in efforts to prevent TB in Tanjung Village were social stigma against TB sufferers, limited supporting facilities, and challenges in ensuring that patients complete their treatment. The solution is that the Tanjung Village government forms a cadre team in each hamlet to ensure that the community is free from TB. With this cadre team, the health of residents can be monitored more effectively, so that prevention and handling of TB can be carried out properly.